222k views
5 votes
Solve the equation. Show your work.
6x-15=3(4x+3)

User Aneri
by
5.3k points

2 Answers

3 votes


6x - 15 = 3(4x + 3)
then you distribute the three
so you would do

3 * 4x = 12x

3 * 3 = 9

6x - 15 = 12x + 9
then you get the variables on the same side

- 6x
on each side so you would have 6x on the right side then you subtract the nine so you would have -24 on the left side so now you have

- 24 = 6x
then you divided by 6 which the answer equals

x = - 4
User Yang Yun
by
5.9k points
5 votes
6x-15=3(4x+3)
Distribute the three to the parentheses
6x-15=12x+9
Transfer the 6 over to the 12 by subtracting it
-15=6x+9
Subtract 9 from 15
-24=6x
Then divide the six by the -24
X=-4
User Claudene
by
6.3k points